(untitled) (Bangladesh Journal of Livestock Research, 2020)
The experiment was conducted to validate an alternative chick brooding device developed for rural poultry farmers in 3 Technology Dissemination Area (TDA) of Poultry Technology Development and Dissemination Project (PTDDP) during winter. The device is a locally designed drum type non-electric chick brooder. A total of 8 poultry farmers in two groups (500 and 1000 chicks) used the specially designed brooder of different sizes. The size of the drum (Height, H- 40.64 × Diameter, D- 45.72) and (H-40.64 × D- 60.96) cm found suitable for 500 and 1000 chicks respectively. The diameter of the hover should double of diameter of the drum with 15 cm long down ward lid around the hover and two bottom outlets for each drum. Manufacturing cost and brooding cost were TK. 2250 and TK. 900 for 500 chicks and TK. 1750 and Tk.1350 for 1000 chicks respectively. The drum designed for 500 and 1000 chicks required 25 kg and 35 kg of saw dust in one time filling that could produce heat for 14 and 22 hours, respectively. Better growth performance as well as profitability was found in non-electric chick brooding groups than the brooding with electricity and diesel burner (locally known as Hericane). It may be concluded that the newly developed non electric chick brooding device could be suitable as an alternative chick brooding system for rural poultry farmers, especially in the areas where there is no electricity supply. Bangladesh J. of Livestock Res. 21-25: 178-182, 2018